The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fendo.2023.1090499
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal body composition and diet on breast milk hormones and neonatal growth during the first month of lactation

Abstract: IntroductionPreterm birth is associated with altered growth patterns and an increased risk of cardiometabolic diseases, with breast milk (BM) being a counteracting factor. Preterm infants also show alterations in adipokines and gut hormones influencing appetite and metabolism. Since these hormones are present in BM, it is possible that their levels may equilibrate deficiencies improving infant growth. We aimed to assess 1) the BM levels of ghrelin, resistin, leptin, insulin, peptide YY, and the gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…On the contrary, it has been previously suggested that leaner mothers could have a greater sensitivity to adiposity [41]. Nevertheless, our results are consistent with the majority of previous studies that found moderate or no correlations between the current maternal or pre-pregnancy BMI and breastmilk leptin [9,10,22,[41][42][43], and that FM% (if assessed) was a stronger predictor of breastmilk leptin compared to BMI [41,44,45]. We observed intriguing results regarding the association between adipose tissue distribution and serum or breastmilk leptin.…”
Section: Serum and Breastmilk Leptin And Maternal Anthropometricssupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, it has been previously suggested that leaner mothers could have a greater sensitivity to adiposity [41]. Nevertheless, our results are consistent with the majority of previous studies that found moderate or no correlations between the current maternal or pre-pregnancy BMI and breastmilk leptin [9,10,22,[41][42][43], and that FM% (if assessed) was a stronger predictor of breastmilk leptin compared to BMI [41,44,45]. We observed intriguing results regarding the association between adipose tissue distribution and serum or breastmilk leptin.…”
Section: Serum and Breastmilk Leptin And Maternal Anthropometricssupporting
confidence: 89%
“…With that said, leptin could beneficially influence the development of the intestinal microbiota [21]. But the effect of leptin on infant growth and body composition has been more widely discussed with ambiguous results [2,18,43]. A recent systematic review revealed that leptin showed consistent negative associations with infant anthropometrics (weight, weight gain, length, BMI z-score, FM%).…”
Section: Possible Implications To the Infant Healthmentioning
confidence: 99%
“…We did not assess body composition or outpatient leptin levels, but other studies have suggested that leptin levels in early childhood could potentially predict later cardiometabolic risk [43]. In a recent investigation, leptin levels were higher in the breast milk of mothers of preterm than term infants, again suggesting an evolutionary role for leptin in infant development, but the differential leptin levels present in breast milk did not negatively impact the neonatal growth of the preterm or term infants [44]. Interestingly, Project Viva investigators obtained longitudinal leptin levels throughout childhood and showed that children with gradually increasing leptin levels had greater adiposity, as would be expected given the production of leptin by adipose tissue, but they also had lower SBP than those that lacked increasing childhood leptin [45].…”
Section: Discussionmentioning
confidence: 93%
“…Another study found no correlation between milk adiponectin and growth outcomes [ 347 ]. Milk IGF-1 concentrations are associated with fat-free mass at 4 months’ corrected age, while milk ghrelin concentrations are associated with neonatal weight gain and linear growth [ 347 , 349 ].…”
Section: Effects Of Nutritional and Pharmacologic Interventions On Gr...mentioning
confidence: 99%